The Politics of Vaccine Diplomacy and Sino-Indonesian Relations - Nur Rachmat Yuliantoro (Global Strategis, 2022)
Since the beginning of 2020, the COVID-19 pandemic has shattered many aspects of human life worldwide. Many believed China was theorigin of the coronavirus that sparked the pandemic. While dealing with the virus domestically, China has also pleaded to help many countries overcome the impact of the pandemic. Within this context, China runs the so-called vaccine diplomacy: providing Chinese-made vaccines to countries in need, including Indonesia. This article argues that although vaccine diplomacy can be seen as evidence of China’s soft power, it is also carried out to serve China’s national interests. Vaccine diplomacy to Indonesia is to demonstrate China’s goodwill and friendship. It is also to help Indonesia recover its economy with the support of Chinese investment and to promote its inﬂuence in the region within the context of great power rivalry with the United States. Sejak awal tahun 2020, pandemi COVID-19 telah menghancurkan banyak aspek kehidupan manusia di seluruh dunia. Banyak yangpercaya Cina adalah asal mula virus Corona yang memicu pandemi. Sembari menangani virus di dalam negeri, Cina juga telah membantubanyak negara mengatasi dampak pandemi tersebut. Sebagai kekuatan besar yang bertanggung jawab, China menjalankan apa yang disebut diplomasi vaksin: menyediakan vaksin buatan China ke negara-negara yang membutuhkan, termasuk Indonesia. Artikel ini berpendapat bahwa meskipun diplomasi vaksin dapat dilihat sebagai bukti soft power China, ia juga dilakukan untuk melayani kepentingan nasional China. Diplomasi vaksin ke Indonesia ditujukan untuk memperlihatkan itikad baik dan persahabatan Cina. Ia juga dimaksudkan untuk membantu Indonesia memperbaiki ekonominya dengan dukungan investasi Cina serta memajukan pengaruhnya di kawasan dalam konteks persaingan kekuatan besar dengan Amerika Serikat.